Network attack detection scheme based on variational quantum neural network - Han Qi; Changqing Gong; Weiqi Guan; Abdullah Gani (Springer, 2022)
During the Borneo Geographic Expedition 2019 in Kadamaian area in Kota Belud, a survey on butterfly fauna was conducted for four days from 21st to 24th October, 2019. Three sites selected for the butterfly sampling were Site 1, Site 2 and Site 4. The methods applied were fruit and carrion baited traps, and aerial netting. A total of 56 individuals were sampled and belonged to 25 species from four families (Nymphalidae, Pieridae, Lycaenidae and Papilionidae). Nymphalidae was the dominant family with Ragadia makuta recorded as the most abundant species. About 60% of the butterflies sampled in the area are forest species, while 40% of the overall species have narrow geographical distribution restricted to Sundaland. The butterfly fauna in Kadamaian area is comparable to other forest types in Sabah in terms of their diversity and species richness. The findings reflected the potential of Kadamaian area as a nature tourism site, and the area could also serve as a corridor for the conservation of flora and fauna as it is located adjacent to Kinabalu Park.